The mission of Nicholas B H Bhengu in a divided and polarised society : an analysis of the life, work and contribuion to mission in southern Africa of an important 20th century pioneer - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Dissertation (PHD)--University of Pretoria, 2008.